ANALYTICAL METHOD DEVELOPMENT AND VALIDATION OF TENILIGLIPTIN IN PHRMACEUTICAL DOSAGE FORM BY RP-HPLC METHOD - Chandana, M.; Rao, Dr.M.Prasad; Samrajyam, B.; Sireesha, K.S.K.D.; premi, V.V.Naga (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
A reverse phase liquid chromatography (RP-HPLC) method has been developed and subsequently validated for the determination of Teneligliptin in Bulk and its pharmaceutical formulation. Separation was achieved with a Zodiac C18 column(250×4.6 mm I.D., 5μm particle size , methanol: acetonitrile (90:10) v/v as mobile phase at a flow rate of 1.0 ml/min , pH 5.2 adjusted with 0.10% orthophosphoric acid and the Column temperature was maintained at 25°C. UV detection was performed at 235 nm and sample temperature was maintained at 5°C with a run time of 10min . The method is simple, rapid, and selective. The described method of Teneligliptin is linear over a range of 25 to 150μg/ml with correlation coefficient of 0.9991 respectively .The method precision for the determination of assay was below 2.0% RSD. The method enables accurate, precise, and rapid analysis of Teneligliptin . It can be conveniently adopted for routine quality control analysis of Bulk and pharmaceutical formulations.